Cross‐sectional and prospective associations of meeting 24‐h movement guidelines with overweight and obesity in preschool children. Issue 7 (31st January 2018) - Berglind, D.; Ljung, R.; Tynelius, P.; Brooke, H. L.
Summary: Background: Cross‐sectional studies report that meeting the newly developed 24‐h movement guidelines (≥60 min moderate to vigorous physical activity (MVPA), ≤120 min screen time and 9–11 h sleep duration) are associated with lower adiposity indicators in children. However, prospective data are absent. Methods: The study sample consisted of 830 children from the PRIMROSE study with GT3X+ accelerometer measured physical activity and parent reported screen time and sleep duration at age 4 years and objectively measured anthropometrics at age 4 and 5 years. The main outcome variables were weight status, body mass index (BMI) and BMI z ‐score at ages 4 and 5 years. Exposure variables were defined as meeting vs. not meeting the 24‐h movement guidelines and combinations of these recommendations. Results: On average, 18.4% of the total study sample met the combination of MVPA, sleep duration and screen time recommendations. In isolation, the MVPA, screen time and sleep guidelines were met by 31%, 63% and 98% of the total study sample, respectively. Adherence to any single recommendation, or any combination of recommendations at age 4 years, was not associated with being overweight or obese nor with BMI and BMI z ‐score at age 4 or 5 years. Conclusions: In contrast to previous cross‐sectional studies, neither individual movement behaviours nor combinations of behaviours at age 4 years was associated with overweight or obesity, BMI or BMI z ‐score at age 4 or 5 years. More prospective data are needed before effects on weight status from meeting the 24‐h movement guidelines are elucidated.